2017
DOI: 10.1249/mss.0000000000001381
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Physical Activity Intensities with Markers of Insulin Sensitivity

Abstract: PA of any intensity may positively influence glucose regulation and insulin sensitivity in individuals at high risk of type 2 diabetes mellitus in a dose-response manner. Further research is required to identify the intensity thresholds at which clinically relevant benefits occur in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…Therefore, along with messages related to accumulating at least 150 min/week of MVPA, individuals should be further encouraged to simply sit less and move more. This has been demonstrated in a recent epidemiological study which showed that physical activity of any intensity influences markers of metabolic health but the higher the intensity, the greater the potential improvement for a given physical activity duration (Jelleyman et al, 2017).…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, along with messages related to accumulating at least 150 min/week of MVPA, individuals should be further encouraged to simply sit less and move more. This has been demonstrated in a recent epidemiological study which showed that physical activity of any intensity influences markers of metabolic health but the higher the intensity, the greater the potential improvement for a given physical activity duration (Jelleyman et al, 2017).…”
Section: Discussionmentioning
confidence: 93%
“…From a pathophysiological point of view, MVPA had demonstrated a negative association with adiposity, that had not been observed in sedentary breaks [36]. Jelleyman et al suggested that the higher the intensity, the greater the potential improvement for a given PA duration in regard to insulin sensitivity assessed by HOMA-IS and Matsuda index [37]. Likewise, Henson et al highlighted the convenience of more intense PA, as they found a higher reduction in chronic inflammation markers (C-reactive protein, interleukin 6) with higher intensity PA [7].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous investigations have typically categorised sedentary behaviour and physical activity (light, moderate, vigorous) using population-dependent thresholds. Using a broader continuum of intensity categories allows for greater insight into the dose-response relationship between physical activity intensity and health outcomes (16). This is important as previous research has typically focused on MVPA, which occupies a very small fraction of the day, if at all.…”
Section: Introductionmentioning
confidence: 99%